MANFAAT HASIL BELAJAR “MELAKUKAN PERAWATAN KULIT WAJAH DEHIDRASI DENGAN TEKNOLOGI” SEBAGAI KESIPAN MENJADI BEAUTY OPERATOR MADYA - Dwi Meilani Marisya; Pipin Tresna Prihatini (Fesyen Perspektif, 2017)
The high demand of the community to the care the skin of the face especially the skin of the face dry because the global warming encourage employers to develop businesses in the plane of beauty so that demand for labor professional in management section beauty the skin the higher, the efforts made by by the government was to develop vocational school especially of beauty the skin. Readiness to work there beauty possible arising after getting knowledge and skills, one of them of competence basic care the skin of the face dehydration. The purpose of this research is to obtain data about the merits of study results do maintenance the skin of the face dehydration with technology as readiness be beauty operator madya. Methods used in research this is the method descriptive with a gatherer data shaped chief. The results of the study showed that of competence basic operate instrument and do maintenance the skin of the face dehydration the majority of respondents know of the benefits of study results do maintenance the skin of the face dehydration and in terms of competence identify the skin of the face dehydration featured more than half of whom respondents know of the benefits of study results do maintenance the skin of the face dehydration with technology as readiness be beauty operator madya. The result of this research expected can be used as the input in developing matter learning.